Novel Mutation of the TINF2 Gene in a Patient with Dyskeratosis Congenita - Panichareon, Benjaporn (Case Rep Dermatol, 2015)
Dyskeratosis congenita (DKC) is a rare inherited disease that is characterized by abnormal skin pigmentation, nail dystrophy and mucosal leukoplakia. DKC is caused by an abnormality in a component of the telomerase and shelterin complexes. TINF2 encodes a protein in the shelterin complex and TERC encodes a component of the telomerase complex. Mutations of both genes have been associated with DKC. This study examined mutations in TINF2